The Supplementation of FloraMax-B11 Did Not Affect the Bile Acid Neosynthesis and the Enterohepatic Circulation in Broiler Chickens - Kouassi R. Kpodo; Atul Chaudhari; Lori L. Schreier; Katarzyna B. Miska; Monika Proszkowiec-Weglarz (Animals, 2022)
Most probiotics possess bile salt hydrolase enzymes and may increase bile acid excretion and negatively affect fat digestion and absorption. Therefore, the study objective was to determine the time course effects of a commercial probiotic (P) FloraMax-B11 (FM) supplementation on bile acid neosynthesis and enterohepatic circulation in broiler chickens. Fertile Ross 708 eggs were incubated under standard commercial conditions. At hatch, chicks (n = 550) were randomly assigned to 5 treatment groups (n = 5 replicates per treatment group) with 22 birds per pen. The 5 treatment groups consisted of: control group (C, normal water from hatch to 35 days of age without supplements); P3, water supplemented with FM for the first 3 days post-hatch followed by normal water until day 35; P10, water supplemented with FM for the first 10 days post-hatch followed by normal water until day 35; P35, water supplemented with FM from hatch to day 35; and AGP, water supplemented with antibiotic growth promoter (AGP) from hatch until day 35. Ileum, liver, and plasma were collected at hatch, days 3, 10, 21, and 35 post-hatch. The relative mRNA expression of genes involved in bile acid synthesis (CYP7A1, CYP8B1, FXR, FGFR4, and FGF19) and transport (ASBT, I-BABP, OSTα, OSTβ, and BSEP) as well as ileal deoxycholic acid and plasma cholic acid were determined. There was no FM and AGP interaction for any of the response criteria. No FM or AGP effects were observed (p > 0.05) for any genes, except FGF19, which expression was increased (p < 0.0001) in AGP compared to P35. No FM or AGP effects were observed (p > 0.05) for levels of deoxycholic and cholic acids. However, all the genes, deoxycholic acid, and plasma cholic acid were affected by age (p < 0.0001). In general, the data indicate that FM did not negatively impact bile acid metabolism and enterohepatic circulation, which appeared to be age dependent. However, more research should be conducted to confirm these results and investigate the effects of FM on bile acid metabolism, fat digestion, and intestinal microbiota in broiler chickens.